Evaluation of workplace learning from an educational psychology perspective - Evelyn Steinberg; Takuya Yanagida; Stephan Marsch (Zeitschrift für Hochschulentwicklung)
This study pursues a learning-centered evaluation approach in higher education. Grounded in the theory of self-regulated learning, this study aimed to evaluate studentsʼ learning processes in a workplace-based course. 188 veterinary students completed the single-item version of the Workplace Learning Inventory in Health Sciences Education. The participants reported frequent use of cognitive learning strategies and moderate use of monitoring and control strategies in the performance phase, as well as partial use of cognitive strategies in the forethought- and reflection phase. They were motivated and experienced positive emotions and a supportive environment. The evaluation provides differentiated insights into the studentsʼ learning and concrete starting points for improving workplace learning.